The Effect of Enzyme Concentration and Hydrolysis Time on the Yield of Microcrystalline Cellulose from Rice Straw - Silvia, Sri; Maharani, Amalina (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2023)
The purpose of this study was to determine the effect of enzyme concentration and hydrolysis time on the yield of microcrystalline cellulose, and to determine whether the results of microcrystalline cellulose examination met the requirements of the British Pharmacopoeia and the United States Pharmacopoeia . The pretreatment process was carried out chemically using 96% alcohol, sodium hydroxide and hydrogen peroxide. The hydrolysis process was carried out enzymatically using the cellulase enzyme produced by the fungus Trichoderma viride , with variations in enzyme concentration of 5, 10 and 15% v/v for 0.5, 1 and 1.5 hours respectively. The highest yield of microcrystalline cellulose was produced from the hydrolysis process with a cellulase enzyme concentration of 5% v/v for 1.5 hours. Based on the two-way ANOVA test, it is known that the enzyme concentration and hydrolysis time have no significant effect on the yield of microcrystalline cellulose. Examination of organoleptic, identification, pH, water solubility, drying shrinkage, and starch absence test showed that the resulting microcrystalline cellulose complied with the requirements of the British Pharmacopoeia and the United States Pharmacopoeia.